Contentious questions and religious dimensions in international intervention - Shuriye, Abdi Omar (Global Journals Inc. (USA), 2012)
Since the beginning of the last decade, there is a renewed attention and interest in the relationship between religion and international intervention. Religion is a belief system, faith and cultural orientation; it is a system of symbols which acts to establish powerful moods and motivations in men by formulating conceptions of a general order of existence and it has direct relation to international intervention. The core objective of this research emanates from the conviction that international intervention has yet to produce sustainable results and role of religion in the process has been marginal. The research therefore, investigates the meagerness, methodologies and the nature of international intervention, as well as the role of religion in its diverse aspects. The central argument of the research leads to the fact that current humanitarian crisis of the world has resulted from the dreadful failure to employ better mechanisms in the implementation levels of any form of intervention.